Airborne pollen levels and drug consumption for seasonal allergic rhinoconjunctivitis: a 10‐year study in France. Issue 1 (28th November 2014) - Caillaud, D. M.; Martin, S.; Ségala, C.; Vidal, P.; Lecadet, J.; Pellier, S.; Rouzaire, P.; Tridon, A.; Evrard, B.
Abstract Background Few time‐series studies, and none lasting longer than 4 years, have investigated the etiology of treated seasonal allergic rhinoconjunctivitis (SAR) on the basis of anti‐allergic medication prescriptions. The aim of this article was to study the short‐term relationship between pollen exposure and drug‐treated SAR over 10 years in an urban area in central France. Methods A SAR case was defined as the association between an oral antihistamine and a local anti‐allergic drug on the same prescription. The relationship between daily changes in pollen concentrations and daily changes in the number of treated SAR cases was analysed using generalized additive models, taking into account confounding factors such as air pollution, weather and days of the week. Results Between 2003 and 2012, the total yearly number of treated SAR cases rose from 7265 to 11 315. The relative risk of treated SAR associated with an interquartile increase in pollen concentration increased significantly for Fraxinus, Betula, Carpinus, Platanus, Poaceae and Urticaceae for the whole pollen season, and for Urticaceae in the first semester. Conclusions The prevalence of treated SAR cases rose by about 55% in 10 years. The study not only confirmed the highly allergenic role of Fraxinus, Betula and Poaceae pollens but also showed a relatively unknown association between treated SAR and Carpinus and Platanus pollens, despite their pollen counts being <1% of overall pollen concentration. It also showed robust correlations with Urticaceae pollens, especially during the first semester, suggesting a potential allergenic role of Parietaria pollination in this non‐Mediterranean area.